DESIGN AND SYNTHESIS OF BENZODIAZEPINES BEARING BENZIMIDAZOLE/BENZOTHIAZOLE AND INDOLE MOIETIES AS A POTENT ANTIMICROBIAL AND ANTIOXIDANT AGENTS - Naraboli, Basavaraj Shivabasappa; Js, Biradar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The present work deals with the synthesis and characterization of biologically active new indole derivatives, namely, 2-((1H-benzo[d] imidazol-2-yl) thio)-N-(4-(4-(1H-indol-3-yl)-8-methyl-1H-benzo[b][1,4]diazepin-2-yl) phenyl) acetamide 3a-d, N-(4-(4-(1H-indol-3-yl)-8-methyl- 1H-benzo[b][1,4]diazepin-2-yl) phenyl)-2-((5-methoxy-1H-benzo[d]imidazol-2-yl) thio) acetamide 4a-d and N-(4-(4-(1H-indol-3-yl)-8-methyl-1H-benzo[b][1,4]diazepin-2-yl) phenyl)-2-(benzo[d]thiazol-2-ylthio) acetamide 5a-d. Methods: All these newly synthesized compounds were screened for their in vitro antimicrobial activity by an agar plate diffusion method, antioxidant activities such as 1,1-diphenyl-2-picrylhydrazyl (DPPH), radical scavenging activity (RSA), ferric ions (Fe3+) reducing antioxidant power (FRAP), and ferrous (Fe2+) metal ion chelating activity. Result: The structures of all the newly synthesized compounds were characterized by their infrared,1H nuclear magnetic resonance, mass spectral studies, and elemental analysis. Compounds 7a and 7b exhibited good RSA at a concentration 100 Î¼g/ml, compounds 6d, 7a-d and 8a-c displayed good FRAP at a concentration 100 Î¼g/ml, compounds 7b-d and 8b-d showed good Fe2+ ion metal chelating activity. Compounds 6b, 6d, 7a-d, and 8a-d exhibited good activity against all the screened bacteria and fungi. Conclusion: Some of the compounds have shown potent antimicrobial activity against all the screened bacteria and fungi, and some have exhibited very good antioxidant activity.